Cdk1 phosphorylation of Esp1/Separase functions with PP2A and Slk19 to regulate pericentric Cohesin and anaphase onset. - Noel Lianga; Carole Doré; Erin K Kennedy; Elaine Yeh; Elizabeth C Williams; Camille Marie Fortinez; Alick Wang; Kerry S Bloom; Adam D Rudner (PLoS Genetics, 2018)
Anaphase onset is an irreversible cell cycle transition that is triggered by the activation of the protease Separase. Separase cleaves the Mcd1 (also known as Scc1) subunit of Cohesin, a complex of proteins that physically links sister chromatids, triggering sister chromatid separation. Separase is regulated by the degradation of the anaphase inhibitor Securin which liberates Separase from inhibitory Securin/Separase complexes. In many organisms, Securin is not essential suggesting that Separase is regulated by additional mechanisms. In this work, we show that in budding yeast Cdk1 activates Separase (Esp1 in yeast) through phosphorylation to trigger anaphase onset. Esp1 activation is opposed by protein phosphatase 2A associated with its regulatory subunit Cdc55 (PP2ACdc55) and the spindle protein Slk19. Premature anaphase spindle elongation occurs when Securin (Pds1 in yeast) is inducibly degraded in cells that also contain phospho-mimetic mutations in ESP1, or deletion of CDC55 or SLK19. This striking phenotype is accompanied by advanced degradation of Mcd1, disruption of pericentric Cohesin organization and chromosome mis-segregation. Our findings suggest that PP2ACdc55 and Slk19 function redundantly with Pds1 to inhibit Esp1 within pericentric chromatin, and both Pds1 degradation and Cdk1-dependent phosphorylation of Esp1 act together to trigger anaphase onset.